The Role of Lymphatics in Cancer as Assessed by Near-Infrared Fluorescence Imaging - Rasmussen, John C. (2011)
The lymphatic system is the secondary circulatory system responsible for fluid homeostasis and protein transport in the body. In addition, because the lymphatic system provides a primary pathway for cancer metastasis, lymph node involvement is routinely used as a determinant in cancer staging. Despite their importance, the lymphatics remain poorly understood, in part because of the historic lack of imaging modalities with sufficient spatial and/or temporal resolution to visualize the fine lymphatic structure and subtle contractile function. In recent years, near-infrared fluorescence (NIRF) imaging has emerged as a new imaging modality to non-invasively visualize the lymphatics and assess contractile lymphatic function in humans following administration of microdose amounts of a NIRF contrast agent. In this contribution, we first review NIRF imaging and its clinical application in sentinel lymph node mapping, intraoperative guidance, and assessing the architecture and contractile function of the lymphatics in health and in cancer-related lymphedema. We then present recent NIRF lymphatic imaging for non-invasive assessment of lymphatics both in preclinical melanoma models and in human subjects with melanoma.